Waste recycling - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
'Interwaste' is the name of a British organisation devoted to the recycling of waste in both Great Britain and developing countries. In Egypt it has set up small units to recycle cloth and plastic, and in Kenya to recycle zinc. Interwaste is run by...